(untitled) (Journal of Intellectual Property Rights (JIPR), 2023)
While courts have traditionally been mindful of the territorial nature of patent rights and thus reluctant to exceed the scope of their jurisdiction, this second installment of the yearlong series, inter alia will try to examine certain global scenarios and conditions that courts consider while granting ASI and A2SI and their application in disputes concerning SEPs, further certain measures would be suggested which the authorsthink might come handy to stop this global race for jurisdiction and how inculcating the same in practice would give the due respect to the national courts of concerned jurisdiction along with incentivizing the parties to focus on key concern issues behind every SEP dispute i.e. the suitable FRAND licensing terms. The present research will also try to convince that such ‘Anti-Anti-Anti-Anti……….Suits Injunction’ saga benefits none, as the same incentivizes a global race to find a court in favorable jurisdiction rather than focusing over the Licensing Negotiations.